IMPROVING THE SYSTEM OF PROTECTION OF THE RIGHTS AND LEGITIMATE INTERESTS OF FARMERS, FARMERS AND LAND OWNERS - Adizov Shuhrat, Salimov Shahzod, Rajabov Azizbek. Bukhara Institute of Natural Resources Management (ZAMONAVIY TA’LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2023)
The demand for agricultural products is also increasing at the same time that the times are rapidly developing today. The cultivation of agricultural products, first of all the supply of the country’s market after which the export to the world market is the most basic task facing agricultural enterprises. To further improve the performance of agricultural enterprises, huge works are being carried out by the state to organize the more efficient use of farms, farm plots.